Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1021/acsomega.0c05075
|View full text |Cite
|
Sign up to set email alerts
|

New Alkyne and Amine Linkers for Versatile Multiple Conjugation of Oligonucleotides

Abstract: Oligonucleotide (ON) conjugates are increasingly important tools for various molecular diagnostics, nanotechnological applications, and for the development of nucleic acid-based therapies. Multiple labeling of ONs can further equip ON-conjugates and provide improved or additional tailored properties. Typically, the preparation of ON multiconjugates involves additional synthetic steps and/or manipulations in post-ON assembly. This report describes the simplified methodology allowing for multiple labeling of ONs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 48 publications
(110 reference statements)
0
10
0
Order By: Relevance
“… Chemical synthesis of multifunctional peptide and/or lipid oligonucleotide conjugates. ( A ) Modified phosphoramidite for the incorporation of two ligands, ( B ) combination of amino-protection and click chemistry allowing the addition of two different ligands [ 200 ], ( C ) base-labile and photolabile protecting groups allow the successive combination of two different ligands [ 201 ]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Chemical synthesis of multifunctional peptide and/or lipid oligonucleotide conjugates. ( A ) Modified phosphoramidite for the incorporation of two ligands, ( B ) combination of amino-protection and click chemistry allowing the addition of two different ligands [ 200 ], ( C ) base-labile and photolabile protecting groups allow the successive combination of two different ligands [ 201 ]. …”
Section: Resultsmentioning
confidence: 99%
“…A tridentate derivative carrying three cyclic RGD peptides have been developed and incorporated into siRNAs showing an increase in inhibitory properties [ 124 ]. In recent research, novel reagents that allow the incorporation of multiple peptides by click chemistry have been developed [ 200 ]. In addition, they allow the preparation of heterofunctional conjugates through a clever use of click chemistry and amino-protection ( Figure 7 B) [ 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…Solid-phase reactions have the advantage of user-friendly procedures which often provide good purity. Due to full biocompatibility and orthogonality, Cu-assisted azide-alkyne cycloaddition (CuAAC) or Copper-free ring-strain promoted azide-alkyne cycloaddition (SPAAC) are among the most popular reactions for ON modifications allowing for fast and efficient conjugation of small molecules, carbohydrates, peptides, hydrophobic compounds (including lipids), aptamers, and antibodies [ 43 ]. Examples of various conjugation strategies of different compounds are described in the following subsections, showing the vast potential of bioconjugation in developing efficient RNA therapeutics.…”
Section: Covalent Conjugation Of Functional Molecules To Rnamentioning
confidence: 99%
“…The attachment of small molecules [79,80] fluorophores [81] like biotin, α-tocopherol and also N-acetylgalactosamin [82] and polyethyleneglycol [83] has demonstrated the importance and usefulness of this strategy to introduce functionalities in oligonucleotides in a simple manner. Recently, a work published by Honcharenko et al [84,85] reported a versatile approach for multiple labeling of oligonucleotides on a solid support. The methodology is compatible with automated solid-phase synthesis and with phosphodiester, as well as phosphorothioate chemistry.…”
Section: Copper (I)-catalyzed Alkyne-azide Cycloaddition (Cuaac)mentioning
confidence: 99%